2020
DOI: 10.1136/bmj.m1190
|View full text |Cite
|
Sign up to set email alerts
|

Covid-19 risks and response in South Asia

Abstract: The region is ill prepared for the crisis that lies ahead

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
63
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(65 citation statements)
references
References 5 publications
0
63
0
2
Order By: Relevance
“…However, critical care capacity remains a problem in all SA countries [ 34 ]. Only a few hospitals have isolation capacity, which can provide intensive care with respiratory support.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, critical care capacity remains a problem in all SA countries [ 34 ]. Only a few hospitals have isolation capacity, which can provide intensive care with respiratory support.…”
Section: Discussionmentioning
confidence: 99%
“…Only a few hospitals have isolation capacity, which can provide intensive care with respiratory support. SA has an estimated 0.7–2.8 critical care beds per 100,000 population [ 34 ]. The number of beds is scarce compared to developed countries in the world.…”
Section: Discussionmentioning
confidence: 99%
“…While this is a simplistic calculation which assumes 0.1% infection rate, with higher infection rate of 1%, the numbers of ventilators required will be approximately 162,000. As of now India does not have that capacity [5]. Similarly, the capacity for intensive care in the country, including that in public health system is limited.…”
Section: Assess the Existing Health Capacity And Anticipate The Surgementioning
confidence: 99%
“…An editorial on the risk South Asia faces in light of SARS-CoV-2 reported that urgent and unified action is needed to avoid a public health catastrophe. 1 An analysis of national preparedness capacities in light of SARS-CoV-2 ended with the stark reality that half of the countries analyzed do not have the adequate capacity to manage an emergency. 2 The Philippines is a country in Southeast Asia that has recently experienced rapid economic growth, pushing to be re-classified as an upper-middle income country.…”
Section: Introductionmentioning
confidence: 99%